Cordia alliodora: a promising tree for tropical agroforestry - Greaves, A; McCarter, P (Oxford Forestry Institute, University of Oxford, 1990)
Cordia alliodora is a fast-growing tree with a high-quality wood. The species is widely distributed in continental tropical America from central Mexico to northern Argentina, a range in latitude of some 50° from approximately 25°N to 25°S. There is also a wide occurrence among the Caribbean islands. Not only does the tree produce high-quality timber but the persistent, tall, straight stem, self-pruning habit and compact crown make it suitable for growing in combination with many agricultural crops. This, combined with the ease with which the species regenerates naturally on cleared sites, has led to its incorporation in numerous agroforestry systems throughout its natural range. C. alliodora can also readily be regenerated artificially by using either seedlings or stumps. Good growth as a plantation species has been achieved in the neotropics, trials in Africa have been promising and it is the basis ofa plantation programme in Vanuatu. On suitable sites dimensions of 30-35 m height and 40-55 cm diameter breast height are predicted for rotations of 20-25 years. However, the choice of provenance is important. Provenance variation over the whole of the species' natural range has not been assessed but substantial data are available for Central America. These show that, in exotic environments, provenances from the seasonally-dry Pacific watershed develop more rapidly at the seedling stage than do provenances from the more humid Atlantic watershed, but within two years of planting in the field this ranking is reversed. The Atlantic group then shows superior growth rates up to 10 years, the greatest age for which information is available. Evidence from plantations exposed to hurricanes and cyclones indicates that C. alliodora probably has above average resistance to stembreak and windthrow, compared with other plantation species, especially during the early years. In the species' natural range, stem canker caused by the rust fungus Puccinia cordiae is economically damaging on some sites. Other pests and diseases have been recorded as problematical locally but not sufficiently to detract from the tree's widespread popularity. Outside its natural range C. alliodora appears to have few serious pests and diseases but mortalities due to a root disease attributed to the fungus Phellinus noxius have given rise to concern in Vanuatu. The timber seasons easily with little degrade. It is dimensionally stable when dry, moderately durable compared with other tropical hardwoods when exposed to fungus attack, and resistance to termites is good. The wood works easily with little dulling of cutting edges to give a very smooth finish. Polishing and staining characteristics are satisfactory. The decorative heartwood has somewhat similar mechanical properties to Swietenia macrophylla. These characteristics have resulted in the timber being widely used in the countries where the species occurs naturally. The wood is popular for light construction, as well as for furniture- and cabinetmaking. It is also used for veneer manufacture, turnery and a wide variety of carvings. As many of the properties of C. alliodora wood are similar to those of S. macrophylla, it might be an acceptable substitute in uses such as boat planking and other boat parts. The resistance to decay indicates a possible role as an alternative timber to several species of cedar in situations requiring durability. An investigation of plantation grown samples from Vanuatu concluded that although the wood is not strong for construction purposes, the combination of stability and durability make it suitable for both indoor and outdoor work. The appearance suggests a use in furniture construction and panelling, and it should be acceptable for flooring where there is light traffic.